Morning-based resistance exercise improves afternoon jumping performance, stretch-shortening-cycle muscle power, and lower limb stiffness in top-level ice hockey players - Kvorning, T.; Karkov, D. S.; Luno, C. S.; Dinesen, N. M.; Jørgensen, A. N.; Gejl, K. D.; Blazevich, A. J.; Aagaard, P. (The Journal of Strength and Conditioning Research, 2026)
Precompetition training (PCT) performed as nonexhaustive bouts of morning-based resistance exercise (e.g., resistance priming) may positively affect afternoon physical performance. Specifically, experimental evidence points toward improved force- and power-related performance. The present study aimed to examine the effect of a morning PCT session on afternoon mechanical muscle function, as reflected by changes in maximal isolated isometric knee extensor (KE) strength (maximal voluntary contraction), and KE rapid force capacity (rate of force development: RFD), countermovement jump (CMJ) kinematics and kinetics, and lower limb stiffness (LLS). Fifteen Danish elite ice hockey players from the U20 National Team (18-20 years) performed (a) a PCT test day consisting of a back squat-lift session of 4 sets of 3 repetitions, with a maximal intentional speed at 50, 65, 75, and 85% 1 repetition maximum, respectively, in the morning (9:00 hours) followed by CMJ and KE testing in the afternoon (15:00 hours), and (b) a control (CON) test day consisting of afternoon (15:00 hours) testing only. Results showed that enhanced stretch-shortening-cycle (SSC) muscle function was observed during CMJ testing after PCT compared with CON (p = 0.05), as evidenced by increases (p < 0.05) in maximal jump height (+3.5% [0.5-6.5]), peak vertical ground reaction force in the descending phase (+5.1% [0.3-9.9]), take-off impulse in the ascending phase (+1.6% [0.2-3.1]), LLS (+23.1 [-4.3 to 50.6]), and mean ascending take-off power (+4.8% [1.7-7.9]). In contrast, PCT did not elicit changes in KE strength or RFD. In conclusion, morning-based PCT in the form of lower-body resistance exercise improves lower limb SSC muscle function later in the day in this cohort of high-level athletes.